Flexible Broadband Terahertz Modulation Based on Strain-Sensitive MXene Material - Liu, Yangqi; Li, Xiang; Yang, Tingting; Liu, Jingyu; Liu, Bin; Shen, Jingling; Zhang, Bo; Wang, Fuhe (Frontiers in Physics, 2021)
A flexible broadband terahertz modulator based on a strain-sensitive MXene material is reported. MXene is shown to have high terahertz wave absorption through experimental testing of various substrate samples. Results show that the THz signal transmission increases with increasing stretching degree, which differs obviously from transmission through pure PVAc substrates. Analysis of the terahertz time-domain spectrum and electrical characterization indicate that the sample’s conductivity decreases with increasing stretching degree. The trend and magnitude of the electrical conductivity results are also very similar to those from the time-domain spectrum. MXene is shown to be a simple, efficient terahertz broadband spectrum modulator with transmittance that can be affected by applying external forces.